Interaction between Human Immunodeficiency Virus Type 1 Reverse Transcriptase and Integrase Proteins - Hehl, Eric A. (American Society for Microbiology, 2004)
Reverse transcriptase (RT) and integrase (IN) are two key catalytic enzymes encoded by all retroviruses. It has been shown that a specific interaction occurs between the human immunodeficiency virus type 1 (HIV-1) RT and IN proteins (X. Wu, H. Liu, H. Xiao, J. A. Conway, E. Hehl, G. V. Kalpana, V. R. Prasad, and J. C. Kappes, J. Virol. 73:2126-2135, 1999). We have now further examined this interaction to map the binding domains and to determine the effects of interaction on enzyme function. Using recombinant purified proteins, we have found that both a HIV-1 RT heterodimer (p66/p51) and its individual subunits, p51 and p66, are able to bind to HIV-1 IN. An oligomerization-defective mutant of IN, V260E, retained the ability to bind to RT, showing that IN oligomerization may not be required for interaction. Furthermore, we report that the C-terminal domain of IN, but not the N-terminal zinc-binding domain or the catalytic core domain, was able to bind to heterodimeric RT. Deletion analysis to map the IN-binding domain on RT revealed two separate IN-interacting domains: the fingers-palm domain and the carboxy-terminal half of the connection subdomain. The carboxy-terminal domain of IN alone retained its interaction with both the fingers-palm and the connection-RNase H fragments of RT, but not with the half connection-RNase H fragment. This interaction was not bridged by nucleic acids, as shown by micrococcal nuclease treatment of the proteins prior to the binding reaction. The influences of IN and RT on each other's activities were investigated by performing RT processivity and IN-mediated 3′ processing and joining reactions in the presence of both proteins. Our results suggest that, while IN had no influence on RT processivity, RT stimulated the IN-mediated strand transfer reaction in a dose-dependent manner up to 155-fold. Thus, a functional interaction between these two viral enzymes may occur during viral replication.